Method for producing hydraulic hardening body
The method improves CO2 fixation and workability in hydraulically cured bodies by using a fluid composition with specific ratios of carbonate and organic set retarder, addressing the limitations of existing technologies in CO2 capture and production efficiency.
Patent Information
- Application Number
- JP2023096504
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-12
- Publication Date
- 2024-12-24
AI Technical Summary
Existing methods for producing hydraulically cured bodies, such as concrete, have limited CO2 fixation and do not consider the relationship between CO2 fixation and workability, resulting in insufficient CO2 capture and reduced workability during production.
A method involving the use of a fluid composition made by kneading water, mixed cement, carbonate, and an organic set retarder, with specific ratios of carbonate and organic set retarder to mixed cement, to produce a hydraulically cured body that includes cement, pulverized blast furnace slag, and γ-CaO·SiO2, enhancing CO2 fixation and workability.
The method achieves a hydraulically cured body with a large amount of CO2 fixation and excellent workability, reducing the need for forced carbonation and allowing for larger structures without size restrictions, while maintaining alkalinity and preventing reinforcing steel corrosion.
Smart Images

Figure 2024178021000006 
Figure 2024178021000007 
Figure 2024178021000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a hydraulically hardened product. [Background technology]
[0002] Fixing CO2 in concrete has been under consideration for some time.
[0003] For example, Patent Document 1 describes a method for producing concrete capable of fixing carbon dioxide, which includes preparing a carbonate of a metal selected from sodium, potassium, and magnesium by reacting a hydroxide of the metal with carbon dioxide, preparing a mixture of the carbonate and water, and mixing the mixture with cement to prepare ready-mixed concrete, and the mixture is prepared so that the concentration of sodium ions in the mixture is 1.0% by weight or more and 9.5% by weight or less when the metal is sodium, the concentration of potassium ions in the mixture is 2.0% by weight or more and 65% by weight or less when the metal is potassium, and the concentration of magnesium ions in the mixture is 1.0 ppm by weight or more and 16.5 ppm by weight or less when the metal is magnesium. Thus, Patent Document 1 describes a method for producing concrete capable of fixing carbon dioxide, which includes setting the concentration of metal ions in a mixture of a predetermined type of carbonate and water to a predetermined range, and mixing the mixture with cement.
[0004] However, the amount of CO2 fixed in the concrete produced by the method described in Patent Document 1 is small. Therefore, there is a demand for a technology that can increase the amount of CO2 fixed in hydraulic hardened bodies such as concrete. Furthermore, Patent Document 1 does not consider at all the relationship between the workability during concrete production and the amount of CO2 fixed. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2021-155311 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a method for producing a hydraulic hardened body which fixes a large amount of CO2 and has excellent workability. [Means for solving the problem]
[0007] [1] A method for producing a hydraulic hardened body, comprising: a mixing step of mixing water, mixed cement, a carbonate, and an organic set retarder to obtain a flowable composition; and a hardening step of hardening the flowable composition obtained in the mixing step to obtain a hydraulic hardened body, wherein the mixed cement contains one or more selected from the group consisting of cement, ground granulated blast furnace slag, γ-CS, and fly ash, and the content ratio of the carbonate to the mixed cement (carbonate content x 100 / mixed cement content) is 8.0% or more and 60.0% or less, and the content ratio of the organic set retarder to the mixed cement (organic set retarder content x 100 / mixed cement content) is 0.05% or more and 2.00% or less. [2] The method for producing a hydraulic hardened body according to the above [1], wherein the carbonate is at least one selected from the group consisting of potassium carbonate, sodium carbonate, lithium carbonate, magnesium carbonate, rubidium carbonate and cesium carbonate. [3] The method for producing a hydraulic hardened body according to the above [1] or [2], wherein the carbonate is one or more selected from the group consisting of potassium carbonate, sodium carbonate and lithium carbonate. [4] The method for producing a hydraulic hardened body according to any one of the above [1] to [3], wherein the organic setting retarder is at least one selected from the group consisting of sodium tartrate, an air-entraining water reducing agent, a high-performance air-entraining water reducing agent, and an oxycarboxylic acid. [5] The method for producing a hydraulic hardened product according to any one of the above [1] to [4], wherein the organic setting retarder is sodium tartrate. [6] The method for producing a hydraulic hardened product according to any one of the above [1] to [5], wherein the carbonate ion concentration in the flowable composition is 0.34% or more and 6.00% or less. Effect of the Invention
[0008] According to the present invention, a method for producing a hydraulic hardened body can be provided which fixes a large amount of CO2 and has excellent workability. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a graph showing the results of measuring the flow values of the flowable compositions of Examples 1 to 4 and Comparative Example 1. [Diagram 2] FIG. 2 is a graph showing the results of measuring the amount of CO2 fixed in the hydraulic hardened bodies of Examples 1 to 4 and Comparative Example 1. [Diagram 3] FIG. 3 is a graph showing the results of measuring the compressive strength of hydraulically hardened bodies cured at 20° C. in Examples 1 to 4 and Comparative Example 1. [Figure 4] FIG. 4 is a graph showing the results of measuring the compressive strength of hydraulically hardened bodies cured at 50° C. in Examples 1 to 4 and Comparative Example 1. [Diagram 5] FIG. 5 is a graph showing the results of measuring the amount of CO2 fixed in the hydraulic hardened bodies of Example 5 and Comparative Example 2. [Figure 6] FIG. 6 is a graph showing the results of measuring the compressive strength of hydraulically hardened bodies at ages of 1 day, 3 days, 7 days, 14 days, and 28 days in Example 5 and Comparative Example 2. [Figure 7] FIG. 7 is a graph showing the results of measuring the flow values at 0 strokes of the flowable compositions of Examples 6 to 7, 10 to 13, 16 to 17, and Comparative Example 3. [Figure 8] FIG. 8 is a graph showing the results of measuring the flow values of 15 strokes of the flowable compositions of Examples 6 to 7, 10 to 13, 16 to 17, and Comparative Example 3. [Figure 9] FIG. 9 is a digital camera photograph of a slump test using the flowable composition of Example 9 immediately after mixing. [Figure 10] FIG. 10 is a digital camera photograph of a slump test using the flowable composition of Example 9 30 minutes after mixing. [Figure 11] FIG. 11 is a digital camera photograph of a slump test using the flowable composition of Example 9 90 minutes after mixing. [Figure 12] FIG. 12 is a graph showing the results of measuring the amount of CO2 fixed in the hydraulic hardened bodies of Examples 6 to 7, 10 to 13, 16 to 17, and Comparative Example 3. [Figure 13] FIG. 13 is a graph showing the results of measuring the amount of CO2 fixed in the hydraulically hardened bodies of Examples 8 to 9 and 15. [Figure 14] FIG. 14 is a graph showing the results of measuring the compressive strength of hydraulically hardened bodies at ages of 2 days, 7 days, 28 days, and 33 days in Examples 6 to 7, 10 to 13, and 16 to 17 and Comparative Example 3. [Figure 15] FIG. 15 is a graph showing the results of measuring the flow values of the flowable compositions of Examples 18 to 20 and Comparative Example 4. [Figure 16] FIG. 16 is a graph showing the results of measuring the amounts of CO2 fixed in the hydraulically hardened bodies of Examples 18 to 20 and Comparative Examples 4 to 5. [Figure 17] FIG. 17 is a graph showing the results of measuring the compressive strength of hydraulically hardened bodies at ages of 2 days, 7 days, and 14 days in Examples 18 to 20 and Comparative Examples 4 to 5. [Figure 18] FIG. 18 is a graph showing the results of measuring the flow values of the flowable compositions of Examples 21 to 27 and Comparative Examples 6 to 8. [Figure 19] FIG. 19 is a graph showing the results of measuring the amount of CO2 fixed in the hydraulically hardened bodies of Examples 21 to 27 and Comparative Examples 6 to 8. [Figure 20] FIG. 20 is a graph showing the results of measuring the compressive strength of hydraulically hardened bodies at ages of 5 days, 7 days, 14 days, and 28 days in Examples 21 to 27 and Comparative Examples 6 to 8. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, a detailed description will be given based on an embodiment.
[0011] The present inventors have considered using carbonate as a raw material of a flowable composition as a CO2 source for fixing CO2 in a hydraulic hardened body. However, it was found that when the content of carbonate in the flowable composition is increased to a level higher than that of the conventional one in order to increase the amount of fixed CO2, the flowability of the flowable composition in a short time is significantly reduced. As a result of intensive research by the present inventors in response to such a new problem, it was found that by adding a predetermined amount of an organic setting retarder to the flowable composition, the flowability reduction in a short time of the flowable composition due to the increase in the amount of carbonate can be suppressed even if the content of carbonate is higher than that of the conventional one, and therefore a hydraulic hardened body with a large amount of fixed CO2 can be produced with excellent workability. The present invention has been completed based on such findings.
[0012] The method for producing a hydraulic hardened body of the present invention includes a kneading step of kneading water, a mixed cement, a carbonate, and an organic set retarder to obtain a flowable composition, and a hardening step of hardening the flowable composition obtained in the kneading step to obtain a hydraulic hardened body, the mixed cement including one or more selected from the group consisting of cement, ground granulated blast furnace slag, γ-CS, and fly ash, and the content ratio of the carbonate to the mixed cement (carbonate content×100 / mixed cement content) is 8.0% or more and 60.0% or less, and the content ratio of the organic set retarder to the mixed cement (organic set retarder content×100 / mixed cement content) is 0.05% or more and 2.00% or less.
[0013] The method for producing a hydraulically hardened body includes a kneading step and a hardening step. The hydraulically hardened body produced by this method is concrete or mortar.
[0014] In the kneading step in the method for producing a hydraulic hardened body, water, a mixed cement, a carbonate, and an organic set retarder are kneaded to obtain a flowable composition. The flowable composition is a cement composition and has flowability.
[0015] The mixed cement constituting the fluid composition contains cement. The mixed cement further contains at least one selected from the group consisting of ground granulated blast furnace slag, γ-C2S (γ-2CaO SiO2, also called γ-belite), and fly ash.
[0016] The cement constituting the mixed cement is preferably Portland cement. Portland cement includes ordinary Portland cement (OPC), as well as early strength, super early strength, moderate heat, low heat, sulfate resistance, and other types, which are specified in JIS R 5210:2019. In the fluid composition, one or more of these various Portland cements may be blended. Among these, it is preferable to use one or two of ordinary Portland cement and early strength Portland cement.
[0017] Ground granulated blast furnace slag is a fine powder as specified in JIS A 6206:2013 "Ground granulated blast furnace slag for concrete". Granulated blast furnace slag is made by quenching molten blast furnace slag, which is produced at the same time as shear iron in a blast furnace, with water or air, and has a basicity of 1.60 or more. Ground granulated blast furnace slag is made by drying and pulverizing this granulated blast furnace slag, or by adding gypsum to it. By replacing part of the Portland cement with ground granulated blast furnace slag, it is possible to reduce carbon dioxide emissions during the cement manufacturing stage.
[0018] The types of ground granulated blast furnace slag are classified according to their specific surface area (cm 2 There are four types according to the molecular weight (Mg) of the polymer, any of which may be used in the present invention. a) Blast furnace slag powder 3000: specific surface area is 2750 or more and less than 3500 b) Blast furnace slag powder 4000: specific surface area is 3500 or more and less than 5000 c) Blast furnace slag powder 6000: specific surface area is 5000 or more and less than 7000 d) Blast furnace slag powder 8000: specific surface area is 7000 or more but less than 10000
[0019] From the perspective of replacing part of the cement with ground granulated blast furnace slag and reducing the amount of cement used, which emits a lot of CO2 during its production, thereby reducing CO2 emissions, it is preferable that the content of ground granulated blast furnace slag in the blended cement be 40.0% or more and 65.0% or less.
[0020] The carbonate constituting the flowable composition is a CO2 source for fixing CO2 in the hydraulic hardened body. From the viewpoint of efficiently reducing CO2 in the atmosphere, the carbonate to be used is preferably a carbonate obtained in the process of Direct Air Capture (DAC), which is a technology for directly capturing CO2 in the atmosphere, or a carbonate obtained by bubbling an aqueous solution of hydroxide with CO2. In the bubbling of CO2, it is preferable to control the bubbling time and the pH of the aqueous solution during bubbling so as not to precipitate hydrogencarbonate in the aqueous solution.
[0021] From the viewpoint of efficiently reducing CO2 in the atmosphere, the source of CO2 (carbon dioxide gas) is preferably exhaust gas from a thermal power plant, exhaust gas from a boiler, exhaust gas containing carbon dioxide emitted in the manufacturing process of other products, high-concentration gas with an increased concentration of carbon dioxide in exhaust gas, etc. Furthermore, the humidity and temperature of these gases may be adjusted.
[0022] The form of the carbonate is not particularly limited, and may be a powder or an aqueous solution (aqueous carbonate solution). For example, the carbonate may be added to the water used for the flowable composition, that is, the so-called mixing water.
[0023] From the viewpoint of increasing the amount of CO2 fixed in the hydraulic hardened body and improving the workability in the manufacturing method of the hydraulic hardened body, the carbonate is preferably one or more selected from the group consisting of potassium carbonate, sodium carbonate, lithium carbonate, magnesium carbonate, rubidium carbonate and cesium carbonate, more preferably one or more selected from the group consisting of potassium carbonate, sodium carbonate and lithium carbonate. The carbonate may be used alone or in combination of two or more.
[0024] The organic set retarder constituting the flowable composition delays the setting time of the flowable composition caused by carbonates, and suppresses the decrease in flowability of the flowable composition in a short time. The metal ions and carbonate ions constituting the carbonates accelerate the hydration reaction of the mixed cement immediately after contact with water, whereas when the organic set retarder is contained in the flowable composition, the promotion of the hydration reaction of the mixed cement can be suppressed by the organic set retarder. If the organic set retarder is not contained in the flowable composition, the flowable composition will harden rapidly in a short time caused by carbonates, making it difficult to apply the hydraulic hardened body.
[0025] From the viewpoint of suppressing the decrease in fluidity of the hydraulic hardened body in a short time and improving the workability in the manufacturing method of the hydraulic hardened body, the organic set retarder is preferably one or more selected from the group consisting of sodium tartrate, AE water reducing agent, high performance AE water reducing agent and oxycarboxylic acid, and more preferably sodium tartrate. The organic set retarder may be used alone or in combination of two or more.
[0026] In addition, the flowable composition may contain optional components such as aggregates (fine aggregates, coarse aggregates) in addition to the essential components of water, mixed cement, carbonate, and organic retarder, as described above, depending on the desired properties of the hydraulic hardened body and the flowable composition, so long as the workability of the manufacturing method of the hydraulic hardened body is not reduced. In the kneading step, the optional components may be kneaded together with the essential components, or the optional components may be added to the kneaded product of the essential components and kneaded.
[0027] Fine aggregate is an aggregate defined in JIS A 5308, JIS A 5005, JIS A 5002 and JIS A 5011. Examples of fine aggregate include crushed sand, sand, river sand, sea sand, crushed lime sand, recycled aggregate, lightweight aggregate, heavy aggregate and the like.
[0028] Coarse aggregate is defined in JIS A 5308, JIS A 5005, JIS A 5002 and JIS A 5011. It is distinguished from the above fine aggregates by the size of the particles, and is classified by whether it passes through a 5mm sieve or not. In practice, fine aggregate is defined as aggregate that passes entirely through a 10mm sieve and 85% or more of its weight passes through a 5mm sieve, and coarse aggregate is defined as aggregate that is 85% or more of its weight retained on a 5mm sieve.
[0029] Regarding the blended cement and carbonate contained in the flowable composition, the content ratio of carbonate to blended cement (carbonate content x 100 / blended cement content) is 8.0% or more, preferably 11.0% or more, and more preferably 20.0% or more. When the content ratio of the carbonate is 8.0% or more, a sufficient amount of CO2 can be fixed in the hydraulic hardened body.
[0030] The carbonate content in the mixed cement is 60.0% or less, preferably 56.0% or less, and more preferably 35.0% or less. When the carbonate content is 60.0% or less, the surface after hardening is not constantly wet, improving the workability in the manufacturing method of the hydraulic hardened body.
[0031] Regarding the mixed cement and the organic retarder contained in the flowable composition, the content ratio of the organic retarder to the mixed cement (content of organic retarder×100 / content of mixed cement) is 0.05% or more, preferably 0.20% or more, and more preferably 0.50% or more. When the content ratio of the organic retarder is 0.05% or more, the setting time of the flowable composition can be delayed, and the workability in the manufacturing method of the hydraulic hardened body can be improved.
[0032] The content of the organic retarder in the mixed cement is 2.00% or less, preferably 1.50% or less, and more preferably 1.00% or less. When the content of the organic retarder is 2.00% or less, excessive delay in the setting time of the flowable composition is suppressed, and the workability in the manufacturing method of the hydraulic hardened body can be improved.
[0033] In particular, since the magnitude of slump loss of the flowable composition is affected by the temperature of the flowable composition, when the temperature of the flowable composition is 20°C, it is preferable that the content of the above-mentioned organic condensation retarder is 0.40% or more and 0.50% or less, and when the temperature of the flowable composition is 30°C, it is preferable that the content of the above-mentioned organic condensation retarder is 0.65% or more and 0.75% or less.
[0034] The carbonate ion concentration in the flowable composition is preferably 0.34% or more, more preferably 1.34% or more, and even more preferably 1.75% or more. When the carbonate ion concentration in the flowable composition is 0.34% or more, a sufficient amount of CO2 can be fixed in the hydraulic hardened body.
[0035] The carbonate ion concentration in the flowable composition is preferably 6.00% or less, more preferably 5.00% or less, and even more preferably 4.65% or less. When the carbonate ion concentration in the flowable composition is 6.00% or less, a decrease in the compressive strength of the hydraulic hardened body after hardening can be suppressed.
[0036] In the hardening step carried out after the kneading step, the flowable composition obtained in the kneading step is hardened to obtain a hydraulic hardened body. The method of hardening the flowable composition in the hardening step is not particularly limited. For example, a known method used in the fields of concrete and mortar can be applied.
[0037] In this way, in the method for producing a hydraulic hardened body of the present invention, carbonate is mixed into the flowable composition as a CO2 source. Therefore, even if the hydraulic hardened body is not subjected to so-called forced carbonation curing, which forcibly promotes the carbonation of the hydraulic hardened body in an environment with a CO2 concentration sufficiently higher than the CO2 concentration in the atmosphere (0.04%), a hydraulic hardened body having a sufficient amount of CO2 fixed can be produced. In addition, since the production method of the present invention can produce a hydraulic hardened body with a large amount of CO2 fixed without performing forced carbonation curing, the time required for carbonation curing can be shortened. Furthermore, since it is not necessary to put the hydraulic hardened body in a facility such as a container for performing forced carbonation curing, there is no size restriction of the hydraulic hardened body according to the size of the carbonation curing facility, and a hydraulic hardened body with CO2 fixed in a larger size than before can be produced. Furthermore, the alkalinity of the hydraulic hardened body can be maintained, and rebar corrosion can be suppressed.
[0038] According to the embodiment described above, by adding a predetermined amount of carbonate and an organic setting retarder to the flowable composition, even if the carbonate content is higher than in the past, it is possible to suppress a decrease in the flowability of the flowable composition in a short period of time that occurs due to an increase in the carbonate content, and as a result, it is possible to produce a hydraulic hardened body with excellent workability and a large amount of CO2 fixation.
[0039] Although the embodiments have been described above, the present invention is not limited to the above embodiments, but includes all aspects included in the concept and scope of the claims of the present disclosure, and can be modified in various ways within the scope of the present disclosure. EXAMPLES
[0040] Next, examples and comparative examples will be described, but the present invention is not limited to these examples.
[0041] (Examples 1 to 4) Potassium carbonate (K), a carbonate, was added to tap water (W) and cooled to room temperature to prepare an aqueous solution, which was then mixed with the various raw materials shown in Table 1 to prepare a flowable composition with the composition shown in Table 2. The carbonate ion concentration in the flowable composition was calculated by dividing the ions contained in the carbonate raw material by the weight of the flowable composition. The flowable composition was then poured into a cylindrical formwork 50 mm in diameter and 100 mm in height, and removed after 2 days of age, and allowed to cure in air (temperature 20°C, humidity 60% or temperature 50°C, humidity 40%) until the specified age was reached. In this way, a hydraulically hardened body was obtained.
[0042] Comparative Example 1 A hydraulic hardened body was obtained in the same manner as in Example 1, except that a flowable composition having the composition shown in Table 2 was prepared by kneading various raw materials shown in Table 1 without using any carbonate.
[0043] FIG. 1 shows the results of measuring the flow value of the flowable composition as the fluidity of the flowable composition. The flow value was measured by conducting a flow test of the flowable composition in accordance with JIS R 5201. As shown in FIG. 1, in the flowable compositions of Examples 1 to 4, the desired flow value was obtained by setting the content ratio of the organic set retarder to the mixed cement at 0.05% or more. In Comparative Example 1, which did not contain carbonate, the desired flow value was obtained by including an AE water reducing agent in an amount equivalent to 1.0% or more of the powder amount.
[0044] The measurement results of the amount of CO2 fixed in the hydraulic hardened body are shown in Figure 2. For the measurement, a 7-day-old hydraulic hardened body was immersed in acetone to stop the hydration reaction, and then the hydraulic hardened body was crushed to 150 μm or less to obtain a powder sample, which was subjected to thermogravimetric analysis up to 1000°C in a nitrogen gas environment. The weight loss between 600 and 800°C obtained by thermogravimetric analysis was attributed to the decarbonation reaction of calcium carbonate, and the amount of CO2 fixed in the hydraulic hardened body was calculated, assuming that the CO2 was fixed in the hydraulic hardened body as calcium carbonate.
[0045] As shown in Fig. 2, the amount of CO2 fixed was greater in the hydraulic hardened bodies of Examples 1 to 4 obtained with flowable compositions containing carbonate, compared to the hydraulic hardened body of Comparative Example 1. Note that the reason that a small amount of calcium carbonate was detected even in Comparative Example 1 obtained with a flowable composition not containing potassium carbonate, which is a carbonate, is thought to be due to the influence of limestone, etc., contained in small amounts as a mixed component of the cement used.
[0046] The measurement results of the compressive strength of the hydraulic hardened body cured at 20°C are shown in Fig. 3, and the measurement results of the compressive strength of the hydraulic hardened body cured at 50°C are shown in Fig. 4. Specifically, the compressive strength of the hydraulic hardened body at ages of 2 days, 7 days, and 14 days was measured according to JIS A 1108:2018 "Test method for compressive strength of concrete". As shown in Figs. 3 and 4, even though the flowable composition contained carbonate, the compressive strength of the hydraulic hardened bodies of Examples 1 to 4 was equal to or higher than that of Comparative Example 1.
[0047] [Table 1]
[0048] [Table 2]
[0049] Example 5 Potassium carbonate (K), which is a carbonate, was added to tap water (W) and cooled to room temperature to prepare an aqueous solution, which was then mixed with the various raw materials shown in Table 1 to prepare a flowable composition with the composition shown in Table 2. The flowable composition was then cast into a cylindrical formwork with a diameter of 100 mm and a height of 200 mm, and sealed and cured (at 20°C) until it reached the specified age. In this way, a hydraulically hardened body was obtained.
[0050] Comparative Example 2 A hydraulic hardened body was obtained in the same manner as in Example 5, except that the various raw materials shown in Table 1 were kneaded without using any carbonate to prepare a flowable composition having the composition shown in Table 2.
[0051] The measurement results of the amount of CO2 fixed in the hydraulic hardened body are shown in FIG. 5. The total carbon amount and the amount of inorganic carbon were measured using a total organic carbon meter (with a solid sample combustion device). In the measurement of the total carbon amount, the hydraulic hardened body aged 7 days was immersed in acetone to stop the hydration reaction, and then the hydraulic hardened body was crushed to 150 μm or less to obtain a powder sample, which was heated to 900°C while passing oxygen through it, and the generated CO2 was measured using a non-dispersive infrared analyzer. In the measurement of the amount of inorganic carbon, phosphoric acid was added to a powder sample prepared in the same manner, and the liberated CO2 was measured. As shown in FIG. 5, the amount of CO2 fixed was increased in the hydraulic hardened body of Example 5 obtained from the flowable composition containing carbonate, compared to the hydraulic hardened body of Comparative Example 2.
[0052] In addition, the results of measuring the compressive strength of the hydraulic hardened body at ages of 1 day, 3 days, 7 days, 14 days, and 28 days in accordance with JIS A 1108:2018 "Testing method for compressive strength of concrete" are shown in Fig. 6. As shown in Fig. 6, the hydraulic hardened body of Example 5 obtained from the flowable composition containing carbonate had a compressive strength equivalent to that of Comparative Example 2.
[0053] Moreover, as in Example 1, the flow test of the flowable composition of Example 5 was carried out in accordance with JIS R 5201, and the result was a desired flow value.
[0054] (Examples 6 to 17, Comparative Example 3) Potassium carbonate (K), which is a carbonate, was added to tap water (W) and cooled to room temperature to prepare an aqueous solution, which was then mixed with the various raw materials shown in Table 1 to prepare a flowable composition having the composition shown in Table 3. The flowable composition was then cast into a cylindrical formwork measuring 100 mm in diameter and 200 mm in height, and sealed and cured (at 20°C) until it reached the specified age. In this way, a hydraulically hardened body was obtained.
[0055] [Table 3]
[0056] As a result of carrying out a flow test on the flowable composition in accordance with JIS R 5201, the flowable compositions of Examples 6 to 17 containing an organic retarder had the desired flow value, whereas the flowable composition of Comparative Example 3 not containing an organic retarder had a smaller flow value than the desired flow value. For example, as shown in Figures 7 to 8, the flow values of the flowable compositions of Examples 6 to 7, 10 to 13, and 16 to 17 were larger than that of Comparative Example 3 not containing an organic retarder.
[0057] Furthermore, for Example 9, a slump test was performed on the flowable composition in accordance with JIS A 1101:2005 "Slump Test Method for Concrete" to evaluate the fresh properties. Fig. 9 is a digital camera photograph of the slump test using the flowable composition of Example 9 immediately after mixing. Fig. 10 is a digital camera photograph of the slump test using the flowable composition of Example 9 30 minutes after mixing. Fig. 11 is a digital camera photograph of the slump test using the flowable composition of Example 9 90 minutes after mixing.
[0058] As shown in Figures 9 to 11, in Example 9, which contains an organic retarder, the slump did not decrease even 90 minutes after mixing, and good fresh properties were ensured. In Comparative Example 3, which does not contain an organic retarder, the slump was already 0 cm 30 minutes after mixing, and the pot life required for construction could not be ensured.
[0059] The hydraulic hardened bodies of Examples 6 to 17 were also measured for their CO2 fixation amount, and as a result, a sufficient amount of CO2 was fixed. For example, FIG. 12 is a graph showing the results of measuring the CO2 fixation amount of the hydraulic hardened bodies of Examples 6 to 7, 10 to 13, 16 to 17, and Comparative Example 3. FIG. 13 is a graph showing the results of measuring the CO2 fixation amount of the hydraulic hardened bodies of Examples 8 to 9 and 15. For these measurements, thermogravimetric analysis was performed using hydraulic hardened bodies with a material age of 7 days in the same manner as in Example 1, and the amount of CO2 was calculated. As shown by these results, the hydraulic hardened bodies of the above Examples fixed a sufficient amount of CO2. The hydraulic hardened bodies of Comparative Example 3 also fixed the same amount of CO2 as those of Examples 6 to 17, but could not ensure good fresh properties as described above.
[0060] The hydraulic hardened bodies of Examples 6 to 17 were also subjected to a compressive strength test, and as a result, they had good compressive strength. For example, Fig. 14 is a graph showing the results of measuring the compressive strength of the hydraulic hardened bodies of Examples 6 to 7, 10 to 13, 16 to 17, and Comparative Example 3 at ages of 2 days, 7 days, 28 days, and 33 days, according to JIS A 1108:2018 "Test method for compressive strength of concrete". As shown in Fig. 14, the hydraulic hardened bodies of these Examples obtained from the flowable composition containing carbonate had good compressive strength.
[0061] (Examples 18 to 20, Comparative Example 5) Potassium carbonate (K) or sodium carbonate (N), which is a carbonate, was added to tap water (W) and cooled to room temperature to prepare an aqueous solution, which was then mixed with the various raw materials shown in Table 1 to prepare a flowable composition with the composition shown in Table 4. The flowable composition was then cast into a cylindrical formwork with a diameter of 100 mm and a height of 200 mm, and sealed and cured (at 20°C) until the specified material age was reached. In this way, a hydraulically hardened body was obtained.
[0062] Comparative Example 4 A hydraulic hardened body was obtained in the same manner as in Example 18, except that a flowable composition having the composition shown in Table 4 was prepared by kneading various raw materials shown in Table 1 without using any carbonate.
[0063] [Table 4]
[0064] The flow test results of the flowable compositions of Examples 18 to 20 and Comparative Example 4 were performed in accordance with JIS R 5201 and are shown in Figure 15. As shown in Figure 15, the flowable compositions of Examples 18 to 20, which contain a predetermined amount of an organic setting retarder, had the desired flow values. In addition, the flowable composition of Comparative Example 5 was very hard and flow measurement was not possible.
[0065] Fig. 16 is a graph showing the results of measuring the amount of CO2 fixed in the hydraulic hardened bodies of Examples 18 to 20 and Comparative Examples 4 to 5. Thermogravimetric analysis was performed using the hydraulic hardened bodies aged 7 days in the same manner as in Example 1, and the amount of CO2 was calculated. As shown in Fig. 16, the hydraulic hardened bodies of Examples 18 to 20 fixed a sufficient amount of CO2.
[0066] 17 is a graph showing the results of measuring the compressive strength of the hydraulically hardened bodies of Examples 18 to 20 and Comparative Examples 4 to 5 at ages of 2 days, 7 days, and 14 days according to JIS A 1108:2018 "Testing method for compressive strength of concrete." As described above, the hydraulically hardened bodies of Examples 18 to 20 were also subjected to compressive strength tests, and as a result, they had good compressive strength.
[0067] (Examples 21 to 27, Comparative Examples 7 to 8) At least one of the carbonates potassium carbonate (K) and sodium carbonate (N) was added to tap water (W) and cooled to room temperature to prepare an aqueous solution, which was then mixed with the various raw materials shown in Table 1 to prepare a flowable composition having the composition shown in Table 5. The flowable composition was then cast into a cylindrical formwork measuring 100 mm in diameter and 200 mm in height, and sealed and cured (at 20°C) until it reached the specified age. In this way, a hydraulically hardened body was obtained.
[0068] Comparative Example 6 A hydraulic hardened body was obtained in the same manner as in Example 21, except that a flowable composition having the composition shown in Table 5 was prepared by kneading various raw materials shown in Table 1 without using any carbonate.
[0069] [Table 5]
[0070] The flow test results of the flowable compositions of Examples 21 to 27 and Comparative Examples 6 to 8 were performed in accordance with JIS R 5201 and are shown in Figure 18. As shown in Figure 18, the flowable compositions of Examples 21 to 27, which contain a predetermined amount of an organic setting retarder, had the desired flow values.
[0071] Fig. 19 is a graph showing the results of measuring the amount of CO2 fixed in the hydraulic hardened bodies of Examples 21 to 27 and Comparative Examples 6 to 8. Thermogravimetric analysis was performed using the hydraulic hardened bodies aged 7 days in the same manner as in Example 1, and the amount of CO2 was calculated. As shown in Fig. 19, the hydraulic hardened bodies of Examples 21 to 27 fixed a sufficient amount of CO2.
[0072] 20 is a graph showing the results of measuring the compressive strength of the hydraulically hardened bodies of Examples 21 to 27 and Comparative Examples 6 to 8 at ages of 5 days, 7 days, 14 days, and 28 days according to JIS A 1108:2018 "Testing method for compressive strength of concrete." As described above, the hydraulically hardened bodies of Examples 21 to 27 were also subjected to compressive strength tests, and as a result, they had good compressive strength.
Claims
1. A kneading step of kneading water, a mixed cement, a carbonate, and an organic retarder to obtain a flowable composition; a hardening step of hardening the flowable composition obtained in the kneading step to obtain a hydraulic hardened body; having The blended cement is a mixture of cement, ground granulated blast furnace slag and γ-C 2 Contains one or more selected from the group consisting of S and fly ash; In the flowable composition, The content ratio of the carbonate to the mixed cement (carbonate content × 100 / mixed cement content) is 8.0% or more and 60.0% or less, A method for producing a hydraulic hardened body, wherein the content of the organic set retarder in the mixed cement (content of organic set retarder x 100 / content of mixed cement) is 0.05% or more and 2.00% or less.
2. The method for producing a hydraulic hardened body according to claim 1, wherein the carbonate is at least one selected from the group consisting of potassium carbonate, sodium carbonate, lithium carbonate, magnesium carbonate, rubidium carbonate and cesium carbonate.
3. The method for producing a hydraulic hardened body according to claim 1, wherein the carbonate is at least one selected from the group consisting of potassium carbonate, sodium carbonate and lithium carbonate.
4. 2. The method for producing a hydraulic hardened body according to claim 1, wherein the organic setting retarder is at least one selected from the group consisting of sodium tartrate, an air entraining water reducing agent, a high performance air entraining water reducing agent and an oxycarboxylic acid.
5. The method for producing a hydraulic hardened body according to claim 1, wherein the organic setting retarder is sodium tartrate.
6. The method for producing a hydraulic hardened body according to any one of claims 1 to 5, wherein a carbonate ion concentration in the flowable composition is 0.34% or more and 6.00% or less.
Citation Information
Patent Citations
Concrete and method for producing the same
JP2021155311A
